2015
DOI: 10.3892/ol.2015.3779
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of esophageal carcinoma undergoing concurrent chemoradiotherapy with quantitative dynamic contrast-enhanced magnetic resonance imaging

Abstract: Abstract. The aim of the present study was to investigate whether quantitative dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) can predict an early response in primary esophageal carcinoma patients undergoing concurrent chemoradiotherapy. A total of 25 patients with who were pathologically confirmed stage II-III esophageal carcinoma underwent quantitative DCE-MRI prior to chemoradiotherapy, and at 3 weeks post-treatment, the quantitative parameters [K trans (volume transfer constant; the rate at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…However, the overall prognosis of esophageal carcinoma remains poor because the initial diagnoses are at later stages . Accurate preoperative staging of esophageal carcinoma has been quite difficult by usual imaging . Computed tomography (CT) has been widely used to identify the location of a cancer, relationship to surrounding organs, and to assess the distant metastasis; however, it cannot depict the specific layer invasion of the esophageal wall due to its poor soft‐tissue resolution .…”
mentioning
confidence: 99%
“…However, the overall prognosis of esophageal carcinoma remains poor because the initial diagnoses are at later stages . Accurate preoperative staging of esophageal carcinoma has been quite difficult by usual imaging . Computed tomography (CT) has been widely used to identify the location of a cancer, relationship to surrounding organs, and to assess the distant metastasis; however, it cannot depict the specific layer invasion of the esophageal wall due to its poor soft‐tissue resolution .…”
mentioning
confidence: 99%
“…It may also provide a tool to assess therapeutic response [36]. The study has also confirmed that the quantitative parameters of DCE-MRI (K trans and Kep) can be used to supervise the early clinical effects of EC, which may lead to more objective and timely assessment of treatment [37]. De Cobelli et al [38] used DWI to assess gastroesophageal tumor response to neoadjuvant treatment and found that there was a negative correlation between changes in the apparent diffusion coefficient (ΔADC) and tumor regression grade.…”
Section: Discussionmentioning
confidence: 80%
“…VS-GR DCE-MRI with three parameters of K trans , K ep and V e had been used in predicting an early response in primary EC patients undergoing concurrent chemoradiotherapy [2]; however, more texture features have not been used to assess the response to nCT treatment for EC. Although some scholars analyzed texture analysis in EC patients, most studies analyzed CT images, only a few adopted MR images.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of esophageal cancer (EC) is rising rapidly worldwide, and it has become the eighth most common cancer [1]. In China, squamous cell carcinoma (SCC) is the main pathological type of EC, and it has high-grade malignancy, rapid progression, poor response to treatment and high recurrence rate [2]. Moreover, the disease is associated with poor prognosis, limited quality of life after surgery [3] and a high incidence of postoperative morbidity and mortality [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation